Perancangan Aplikasi Pemesanan Makanan Berbasis Android - Wedi, Surya; Widyarto, Setyawan (Proceedings of the Informatics Conference, 2022)
Javanese Restaurant application that will be developed is an Android-based application. The application can be used to order food and drinks online at a Javanese restaurant, Bebek Kaleyo. Customers who have installed the application can select the menu provided in the application. Customers may order the food and ask to deliver by courier or collect from the restaurant. Payment can be done with a bank transfer or another alternative payment method. Once payment is successful the server will send the menu ordered and payment receipt to the customer in the form of a QR Code. The Code is used to verify the order in the restaurant until the delivery to the customers. All the processes are connected to and updated in the server.